COVID-19 and Guillain–Barré Syndrome: A Case Report and Review of Literature - Zito, Antonio; Alfonsi, Enrico; Franciotta, Diego; Todisco, Massimiliano; Gastaldi, Matteo; Cotta Ramusino, Matteo; Ceroni, Mauro; Costa, Alfredo (Frontiers in Neurology, 2020)
During the recent Coronavirus disease 2019 (COVID-19) outbreak in Northern Italy, we observed a 57-year-old man developing Acute Motor-Sensory Axonal Neuropathy, a variant of Guillain-Barré syndrome (GBS), twelve days after severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection. Similarly to other bacterial and viral infections, dysregulation of the immune system due to post-infectious mechanisms, such as the molecular mimicry, could lead to an indirect damage of the peripheral nervous system related to SARS-CoV-2. GBS causes motor dysfunctions that are not easily recognizable in non-neurological settings or in patients requiring ventilatory assistance. Several reports also suggested that GBS and Miller Fisher syndrome (MFS) could be neurological complications of COVID-19. Therefore, we performed a review of the 29 articles so far published, describing 33 GBS cases and five MFS cases associated with SARS-CoV-2 infection. We recommend awareness of this rare, but treatable, neurological syndrome, which may also determine a sudden and otherwise unexplained respiratory deterioration in COVID-19 patients.